Effect of medium composition and cultural condition on cellulase production by Aspergillus terreus - Shahriarinour, Mahdi; Abdul Wahab, Mohd Noor; Mohamad, Rosfarizan; Mustafa, Shuhaimi; Ariff, Arbakariya (Academic Journals, 2011)
The effect of medium composition and environmental condition on the production of cellulase by Aspergillus terreus was investigated using shake flask culture with oil palm empty fruit bunch (OPEFB) as substrate. The highest activity of FPase (0.76 U ml-1), CMCase (8.64 U ml-1) and β-glucosidase (6.81 U ml-1) was obtained in medium containing 6 g L-1 yeast extract and 10 g L-1 delignified OPEFB fiber. In fermentation with the addition of Tween 80 (2 ml L-1) as surfactant, the production of cellulase was increased by two-fold as compared to fermentation without surfactant. Cellulase production by A. terreus was also enhanced with the addition of calcium chloride (3 mM) and magnesium sulfate (5 mM) in the medium. Optimum pH and temperature for cellulase production by A. terreus was 5.5 and 28°C, respectively. Cellulase production in agitated shake flask fermentation at 200 rpm was four times higher as compared to fermentation in static flask.